2020
DOI: 10.1101/2020.10.14.339499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MaveRegistry: a collaboration platform for multiplexed assays of variant effect

Abstract: Multiplexed assays of variant effect (MAVEs) are capable of experimentally testing all possible single nucleotide or amino acid variants in selected genomic regions, generating 'variant effect maps', which provide biochemical insight and functional evidence to enable more rapid and accurate clinical interpretation of human variation. Because the international community applying MAVE approaches is growing rapidly, we developed the online MaveRegistry platform to catalyze collaboration, reduce redundant efforts,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The MAVE community is making progress in developing assays with high dynamic range and high predictive value. [37][38][39][40] However, addressing the lack of benign and pathogenic control variants for validation is more challenging. A perfect assay must have at least 19 control benign and pathogenic variants for validation to achieve strong benign and pathogenic functional evidence, whereas at least 11 benign and pathogenic variants are required for an assay to achieve moderate evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The MAVE community is making progress in developing assays with high dynamic range and high predictive value. [37][38][39][40] However, addressing the lack of benign and pathogenic control variants for validation is more challenging. A perfect assay must have at least 19 control benign and pathogenic variants for validation to achieve strong benign and pathogenic functional evidence, whereas at least 11 benign and pathogenic variants are required for an assay to achieve moderate evidence.…”
Section: Discussionmentioning
confidence: 99%
“…DMS has been widely adopted to explore effects of amino acid variation using a variety of different experimental phenotypes, such as protein abundance, activity or general cellular fitness 5 . However, while the number of proteins that have been characterized through DMS grows constantly 7,8 , and use of these methodologies and coordination between groups is increasing through the Atlas of Variant Effects Alliance 9…”
Section: Introductionmentioning
confidence: 99%
“…Well-established functional assays can provide strong evidence for classification of a variant as either pathogenic or benign 3,8 , but such results are typically unavailable for rare missense variants. Although "variant effect mapping" technologies have been established to proactively determine the functional effects of many variants in parallel [9][10][11] , a variant effect map is available for only ~1% of human disease-associated proteins 12 .…”
Section: Introductionmentioning
confidence: 99%
“…They also had limited ability to carry out unbiased evaluation for predictors (e.g., DeepSequence) that had used variant effect map data in model training. Although Livesey and Marsh found that variant effect maps were typically more accurate than predictors of pathogenicity, a variant effect map is currently available for only ~1% of human disease-associated proteins [26].…”
Section: Introductionmentioning
confidence: 99%